Portable IoT-Based Disinfection Box - Muda, Muhammad Ikmal; Mohd Shah, Shaharil (Journal of Electronic Voltage and Application, 2023)
The COVID-19 pandemic is an ongoing global health event that began in 2019. It is caused by a novel strain of coronavirus known as SARS-CoV-2. Bacteria and viruses can cause illness in human. Therefore, a Portable IoT-based Disinfection Box is developed in this work to disinfect small electronic devices such as smartphone, smartwatch or even a 13-inch tablet, that may come into contact with bacteria and viruses. There are three special features of this Disinfection Box which are the timer itself, Web Interface Monitoring, portable and spacious with dimensions of 29 × 18 × 14 cm3. The ESP32 Wi-Fi module with NodeMCU-32S Base module as a microcontroller is used in this work and it controls the 2-channel Relay in order to turn ON and OFF the UV-C LED light strip. Besides that, it is also connected to the LCD display with I2C module to display the real-time of disinfection process. The Dashboard of Arduino IoT Cloud allows the user to control and monitor the operation of disinfection process. When a small electronic device is placed inside the Disinfection Box, UV-C LED light strip is turned on to begin the disinfection process. The effectiveness of the UV-C LED light strip is investigated by using the Petri dish with agar. It is shown from the experimental procedures that 10-minute disinfection time provided by the Disinfection Box is sufficient to disinfect small electronic devices such as smartphone and smartwatch. This is based on the great reduction of bacteria colonies on the agar in Petri dish after being kept in a dark place with room temperature for 4 days.